Curcumin mediates oxidative stress to play an anti-fibrotic role, focusing on liver, renal, myocardial and pulmonary fibrosis - Yu, Shishuang; Pu, Jufang; Liu, Ke; He, Cuifang; Yang, Feifei; Chen, Ke; Yang, Xiuli; Zhu, Yi; Jiang, Jun; Luo, Maocai; Liu, Xiao; Zhang, Chuantao; et al. (Frontiers in Pharmacology, 2025)
BackgroundCurcumin is a natural polyphenolic compound that originates from turmeric (Curcuma longa L., Linnaeus, Zingiberaceae), a traditional medicinal herb. It is widely recognized for its strong antioxidant properties.ObjectiveThis comprehensive review aims to delineate the recent progress in comprehending the role of curcumin in modulating oxidative stress and exerting an anti-fibrotic effect, with a particular focus on liver, renal, myocardial, and pulmonary fibrosis.MethodsA systematic review of the literature was conducted via the PubMed, Web of Science, Google Scholar, and China National Knowledge Infrastructure, covering 2000 until 2024. A systematic review identified studies examining curcumin’s regulation of oxidative stress pathways in therapeutic strategies for multiple fibrotic disorders, which were analyzed to synthesize current evidence.ResultsIn recent years, the application of curcumin for the clinical management of fibrotic diseases in a variety of clinical applications has been extensively investigated. Accumulating evidence suggests that curcumin can exert antifibrotic effects by ameliorating oxidative stress through the modulation of various signaling pathways such as regulating reactive oxygen species (ROS), nuclear factor erythroid-2-related factor 2 (NRF2), peroxisome proliferator-activated receptors (PPAR), transforming growth factor- β1 (TGF-β1). In this review, we investigate the pharmacokinetics of curcumin, the relationship between oxidative stress and the pathogenesis of fibrosis, and summarize the related studies of curcumin in the treatment of fibrotic diseases by regulating oxidative stress.ConclusionThis comprehensive review elucidates curcumin’s antifibrotic potential and explores its translational applications in developing novel therapeutic strategies to combat fibrotic pathologies, supported by mechanistic evidence that informs safer, more effective treatment paradigms.